2022
DOI: 10.1530/eor-22-0053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and safety of aspirin and other anticoagulants for venous thromboembolism prophylaxis after major orthopedic surgery: a systematic review and meta-analysis of randomized clinical trials

Abstract: Purpose Patients undergoing major orthopedic surgeries, such as total hip replacement (THR), total knee replacement (TKR), and trauma surgery, are at an elevated risk of venous thromboembolism (VTE), causing significant morbidity and mortality. Previous studies have investigated aspirin as a thromboprophylactic agent for arthroplasty, besides trauma surgery. Therefore, we sought to analyze the efficacy of aspirin compared to that of other anticoagulants for VTE prophylaxis in patients undergoing major orthop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…This result is similar to that of a large observational cohort ( Richardson et al, 2019 ). However, previous meta-analyses such as the study conducted by Matharu et al (2020) and the study conducted by Singjie et al (2022) , comparing the efficacy and safety of aspirin and other anticoagulants, including oral anticoagulants and LMWH, in the prevention of VTE after hip and knee replacement or orthopedic trauma, have shown that there is no statistically significant difference in the prevention of VTE between aspirin and anticoagulants. These results differed from our findings.…”
Section: Discussionmentioning
confidence: 98%
“…This result is similar to that of a large observational cohort ( Richardson et al, 2019 ). However, previous meta-analyses such as the study conducted by Matharu et al (2020) and the study conducted by Singjie et al (2022) , comparing the efficacy and safety of aspirin and other anticoagulants, including oral anticoagulants and LMWH, in the prevention of VTE after hip and knee replacement or orthopedic trauma, have shown that there is no statistically significant difference in the prevention of VTE between aspirin and anticoagulants. These results differed from our findings.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, two systematic reviews of randomised control trials by Matharu et al and Singjie et al noted that Aspirin did not differ significantly from other anticoagulants in terms of safety and clinical effectiveness after THA [ 25 , 30 ]. However, the recent CRISTAL study from Australia reported significantly higher rates of symptomatic VTE with Aspirin (3.45%) compared with enoxaparin (1.82%), both of which were significantly higher than our reported 1.11%, with fewer patient numbers [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aspirin had the same effects, but overall quality assessments of selected RCTs ranged from low to high quality, and most RCT evidence showed a high risk of bias. [9,[30][31][32] Another meta-analysis reported no statistically significant differences between aspirin and enoxaparin for DVT and PE; overall evidence quality was low and validation is required from more RCTs. [33] Coveney [34] et al supported aspirin as effective in preventing symptomatic VTE after THA in 8885 patients receiving aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, aspirin has demonstrated high safety profiles due to its convenience and cost effectiveness; a large randomized placebo-controlled DVT prevention study after 13,356 hip fractures and 4088 knee replacements showed that aspirin reduced PE risk and prevented DVT after major orthopedic surgery, thereby confirming that aspirin had potential as a routine prophylactic agent for VTE formation in clinical practice. [ 8 ] The role of aspirin in preventing VTE in major orthopedic surgery was previously reported in a 2022 meta-analysis, [ 9 ] but the emergence of new large-scale randomized controlled trials (RCTs) and differences across studies have led to data equivocation. [ 10 , 11 ] Therefore, we reanalyzed the efficacy and safety of aspirin when compared with other anticoagulants in preventing VTE in major orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%